Reflections on the definition of quality of education and a focus on its significance for contemporary Muslim societies - Jebli, Samir; Foulad, Rida; Amellah, Saif; Sahib, Amal-Oudiî; Bouaziz, Abdelhaq (Edelweiss Applied Science and Technology, 2024)
The quality of education is considered a pillar of development and prosperity in contemporary societies. This importance has given rise to a titanic quantity of scientific publications. However, there is no consensus on the meaning of quality in education. The present literature review aims to show the different approaches used to discuss educational quality in the absence of a universal definition. The quantitative analysis in this work has been conducted to formulate important remarks, among which, the existence of confusion between education and teaching and the importance given to employability as a major objective. To remedy the various shortcomings and flaws, and in order to properly define the quality of education, a change of approach was called for. To define the ideal of education, a philosophical approach was taken as a starting point. In addition, a reflection on how this quality should be defined for contemporary Muslim societies was proposed.